Levels of job satisfaction amongst Malaysian academic staff - Noordin, Fauziah; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
A study of job satisfaction of academic staff of a public university in Malaysia used the 7-item general satisfaction scale in a survey to determine the level of job satisfaction of the academic staff. The results indicated that overall the academic staff of the university has a moderate level of job satisfaction. In addition, current status, marital status, age and salary appear to have significant impact on the respondents’ level of job satisfaction. Implications on the study’s findings to the management of the university are also discussed.